Clinical evidence for repurposing chloroquine and hydroxychloroquine as antiviral agents: a systematic review. (August 2020) - Rodrigo, C.; Fernando, S.D.; Rajapakse, S.
Abstract: Background: Repurposing hydroxychloroquine (HCQ) and chloroquine (CQ) as antiviral agents is a re-emerging topic with the advent of new viral epidemics. Aims: To summarize evidence from human clinical studies for using HCQ or CQ as antiviral agents for any viral infection. Sources: PubMed, EMBASE, Scopus, Web of Science for published studies without time or language restrictions; Cochrane Clinical Trial Registry and Chinese Clinical Trials Registry for trials registered after 2015; MedRxiv for preprints within the last 12 months. Content: Study eligibility criteria were interventional and prospective observational studies (with or without a control group). Participants were adults and children with a confirmed viral infection. Interventions included the use of CQ or HCQ as antiviral agent in one or more groups of the study. Two authors independently screened abstracts, and all authors agreed on eligible studies. A meta-analysis was planned if studies were available which were similar in terms of participants, intervention, comparator and outcomes. Nineteen studies (including two preprints) were eligible (HIV 8, HCV 2, dengue 2, chikungunya 1, COVID-19 6). Nine and ten studies assessed CQ and HCQ respectively. Benefits of either drug for viral load suppression in HIV are inconsistent. CQ is ineffective in curing dengue (high-certainty evidence) and may have little or no benefit in curing chikungunya (low-certainty evidence). The evidence for COVID-19 infection is rapidly evolving but at this stage we are unsure whether either CQ or HCQ has any benefit in clearing viraemia (very-low-certainty evidence). Implications: Using HCQ or CQ for HIV/HCV infections is now clinically irrelevant as other effective antivirals are available for viral load suppression (HIV) and cure (HCV). There is no benefit of CQ in dengue, and the same conclusion is likely for chikungunya. More evidence is needed to confirm whether either HCQ or CQ is beneficial in COVID-19 infection.